Penciptaan Suasana Religius Di Madrasah Tsanawiyah Negeri Model Samarinda - Khairul Saleh (FENOMENA, 2013)
As an education institute that typically Islamic, madrasah plays an important role in the process of pupil personality establishment, because of that through madrasah education the parents hope that their children have two abilities at once, not only science and technology (iptek) but also has a high personality and commitment of their religion (imtaq). While in the practice, can be understood that the madrasah actualization as an Islamic typically schools is still far from what is hoped. The understanding of the characteristic of Islam is still understood partially, is only seen from the outside aspect (exoteric) and symbolic. This will not ever exist if madarasah  does not do the innovations in actualizing the function as an Islamic madrasah and to fulfill the parents hope.